Virtual Learning in English Course at LKP Mahesa Institute Kampung Inggris Pare Kediri - Wiwin Yulianingsih; Soedjarwo Soedjarwo; Rivo Nugroho; Maria Veronica Roesminingsih; Monica Widyaswari (JPPM (Jurnal Pendidikan dan Pemberdayaan Masyarakat), 2021)
This study aims at describing virtual learning in English courses at LKP Mahesa Institute Kampung English Pare Kediri. This study employs a quantitative research design. The population and sample included 100 people with the ones taking courses at LKP Mahesa Institute Kampung Inggris Pare Kediri as the research subjects. The sampling technique used in this research is total sampling. The data were analysed using descriptive statistics in the form of percentages. The overall research results show that virtual learning with the approach of creating and sharing interactive content in English courses is categorized good with a percentage of 78.42%. These results are supported by the suitability of the results in each of the sub-variables, namely teaching quality, teaching level, incentive, and time. In this case, virtual learning with the approach of creating and sharing interactive content in English courses is quite effective. Therefore, this learning system is expected to be one of the new approaches that can be applied in English courses, especially during the Covid-19 pandemic which applies distance learning.